2013
DOI: 10.1371/journal.pone.0072138
|View full text |Cite
|
Sign up to set email alerts
|

S100A8 and S100A9 Induce Cytokine Expression and Regulate the NLRP3 Inflammasome via ROS-Dependent Activation of NF-κB1

Abstract: S100A8 and S100A9 are cytoplasmic proteins expressed by phagocytes. High concentrations of these proteins have been correlated with various inflammatory conditions, including autoimmune diseases such as rheumatoid arthritis and Crohn’s disease, as well as autoinflammatory diseases. In the present study, we examined the effects of S100A8 and S100A9 on the secretion of cytokines and chemokines from PBMCs. S100A8 and S100A9 induced the secretion of cytokines such as IL-6, IL-8, and IL-1β. This secretion was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
188
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(205 citation statements)
references
References 71 publications
13
188
1
3
Order By: Relevance
“…[59][60][61] In fact, it has been widely reported that NF-kB is activated by H 2 O 2 and other oxidants. [62][63][64][65][66] In the present study, we demonstrated that H 2 O 2 mediates its action through the ALK5/ Smad3/NF-kB intracellular pathway. These findings suggest possibly that the NF-kB transcription factor is involved in the modification of protein expression that is induced by oxidative stress.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…[59][60][61] In fact, it has been widely reported that NF-kB is activated by H 2 O 2 and other oxidants. [62][63][64][65][66] In the present study, we demonstrated that H 2 O 2 mediates its action through the ALK5/ Smad3/NF-kB intracellular pathway. These findings suggest possibly that the NF-kB transcription factor is involved in the modification of protein expression that is induced by oxidative stress.…”
Section: Discussionsupporting
confidence: 57%
“…Taken together, the results shown here provide evidence that oxidative stress is a crucial factor in inducing the conversion of ECs into myofibroblasts through a TGF-bdependent mechanism that produces changes in EC protein [62][63][64][65][66] This gene expression could be involved in the H 2 O 2 -induced conversion of ECs into myofibroblasts because inhibition of NF-kB using IKK-16 inhibited the conversion. (iii) Our results showed that H 2 O 2 induces the phosphorylation of p38MAPK.…”
Section: Discussionsupporting
confidence: 56%
“…S100A8/S100A9 heterodimers activate both NF-kB and NLRP3 inflammasome assembly via a NOX/ROS-dependent mechanism. 23,[44][45][46] Intracellularly, S100A8/9 heterodimers serve as a scaffold for the membrane assembly and activation of the NOX complex, 47,48 which generates ROS via transfer of electrons across membranes to generate superoxide. 49 As also shown here, NOX regulates both priming and activation of NLRP3 inflammasomes, including the activation of caspase-1 and IL-1b secretion.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,20,21 NLRP3 is activated by diverse DAMP signals, including S100A9 homodimers and S100A8/9 heterodimers that function as alarmins that converge upon NADPH oxidase to generate reactive oxygen species (ROS). [21][22][23] Here, we show that S100A9 and ROS, generated in response to NLRP3 inflammasome activation or somatic gene mutations, serve as DAMP signaling intermediates responsible for inflammasomemediated pyroptosis and b-catenin activation in MDSs. Remarkably, disabling this inflammasome circuit restores effective hematopoiesis in MDSs.…”
Section: Introductionmentioning
confidence: 87%
“…Caspase-1 Assay-Caspase-1 activity was measured with the caspase-1 colorimetric assay kit (R&D Systems) as described previously (24). Briefly, 4 ϫ 10 6 cells were stimulated with agonists for the indicated periods of time and lysed with ice-cold lysis buffer after incubation for 10 min on ice.…”
Section: Methodsmentioning
confidence: 99%